PERANAN KONSTITUSI DALAM MENJAGA INDEPENDENSI DAN AKUNTABILITAS LEMBAGA NEGARA DI TENGAH DINAMIKA POLITIK INDONESIA MASA KINI - Elsy Anthoneta Joltuwu (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2026)
This article examines the crucial role of the Constitution, particularly the 1945 Constitution of the Republic of Indonesia (UUD NRI 1945), in ensuring the independence and accountability of state institutions amid the turbulence and dynamics of contemporary Indonesian politics. The amendments to the 1945 Constitution have produced a complex institutional architecture, marked by the emergence of independent state bodies such as the Constitutional Court, the Judicial Commission, and the Audit Board of Indonesia. Although, at the normative level, the Constitution provides a strong foundation for the separation of powers and the mechanism of checks and balances, political practices dominated by oligarchic interests and polarization have the potential to undermine this constitutional mandate. This study employs a normative-empirical approach by analyzing constitutional provisions related to institutional independence and accountability, as well as examining the empirical challenges faced in their implementation. The findings indicate that the strength of the Constitution as a “democratic safeguard” largely depends on political commitment and the moral integrity of state actors in interpreting and implementing its mandates. The Constitution functions dually as a source of legitimacy for institutional independence and as an instrument for enforcing accountability, thereby making it a decisive factor in shaping the quality of modern governance in Indonesia.